Engineering the Human Human Enhancement Between Fiction and Fascination - Koops, Bert Jaap.; L<U+00fc>thy, Christoph H.; Nelis, Annemiek.; Sieburgh, Carla.; Jansen, J.P.M.; Schmid, Monika S. (Springer Berlin Heidelberg : Imprint: Springer, 2013)
In this book, the topic of human enhancement is discussed from a variety of perspectives <U+0013> genetic, medical, philosophical, literary, sociological, and legal. It addresses not only those aspects that most immediately come to mind when one thinks of <U+0018>human enhancement,<U+0019> such as genetic engineering, cloning, artificial implants and artificial intelligence, but also less obvious aspects including evolutionary perspectives in connection with the prolongation of the human lifespan, plastic surgery since its beginnings, and questions such as whether the distinction between <U+0018>natural<U+0019> and <U+0018>artificial<U+0019> can really be drawn at all and how it has been conceived across the ages, or what the legal implications of recent developments and techniques are. Many chapters draw parallels to the representation of these developments in popular culture, from Jules Verne through Aldous Huxley to the movie Gattaca, addressing the hopes and fears that they reflect along with the question of how realistic they are. While all chapters were written by scientists at the top of their respective fields, all are accessible to a non-specialist audience and eminently readable. They represent a state-of-the art overview of questions that are of interest to a broad audience. The book thus targets a non-specialist audience with an interest in philosophical, sociological, scientific and legal issues involved in both traditional and recent matters concerning the desire of mankind to improve itself. It is unique in that it brings together all these aspects within a coherent and cohesive work.